Continuous Normothermic Machine Perfusion for Renovation of Extended Criteria Donor Livers Without Recooling in Liver Transplantation: A Pilot Experience - Chen, Zhitao; Hong, Xitao; Huang, Shanzhou; Wang, Tielong; Ma, Yihao; Guo, Yiwen; Huang, Changjun; Zhao, Qiang; Guo, Zhiyong; He, Xiaoshun; Ju, Weiqiang; Chen, Maogen (Frontiers in Surgery, 2021)
Background: Ischemia injury affects the recovery of liver allograft function. We propose a novel technic aimed to avoiding second ischemic injury by transplanting extended criteria donor (ECD) liver directly under normothermic machine perfusion (NMP) without re-cooling. In this study we have a study of 2 cases to evaluate the efficacy and safety of this technic. Methods: Perioperative characteristics and postoperative outcomes of 2 recipients of an ECD liver were analyzed. Both were performed with a continuous normothermic machine perfusion without re-cooling. Result: In case 1, The cause of donor’s death was anoxia, and the donor liver was with hypernatremia before procurement. The recipient was diagonsed with decompensated cirrhosis. The model for end-stage liver disease (MELD) score was 38. In case 2, donor liver was from Donor after cardiac death (DCD) and with elevated aspartate aminotransferase (AST) and alanine aminotransferase (ALT). The recipient was diagnosed with acute hepatic failure. The MELD score was 35. Two donor livers were both maintained under NMP and then transplanted into donor without recooling. The peak ALT and AST after surgery were 452 U/L and 770 U/L in case 1, and 100 U/L and 592 U/L in case 2, respectively. Neither early allograft dysfunction (EAD) nor primary graft nonfunction (PNF) was presented in these 2 cases. Conclusion: In conclusion, our results demonstrate that continuous NMP without re-cooling is with efficacy and safety for LT with extended criteria donor livers. Further investigations of this technic will be made to achieve promising results.